Eugenics Redux: “Reproductive Benefit” as a Rationale for Newborn Screening - Paul, Diane B. (The Hastings Center report, 2018)
In recent years, as newborn screening has expanded to include conditions for which treatment is questionable, new rationales for screening have proliferated. One such rationale is the potential reproductive benefit to parents from the detection of a genetic condition or carrier status in infants. An unanticipated consequence of invoking knowledge of reproductive risk as a major benefit of screening has been to open newborn screening to the charge that it constitutes state-sanctioned eugenics. Thus, an endeavor that had been viewed as the converse of state programs of selective breeding has come to be seen in some quarters as yet another of its incarnations. The result has been serious and self-inflected harm to the reputation of newborn screening programs.